Time and temperature regime of continuous grain coarsening in an ECAP-processed Al(0.1 wt.% Sc) alloy - Bommareddy, A.; Quadir, Md Zakaria; Ferry, M. (Elsevier B.V., 2012)
An equiaxed, submicron grain size distribution was generated in an Al(0.1 wt.% Sc) alloy by processing through equal channel angular pressing followed by a low temperature pre-ageing heat treatment. The alloy was subsequently annealed for various times at 300, 350, 400 and 450 °C for investigating the thermal stability of the deformation microstructure. It was found that up to 400 °C, the submicron grain structure coarsens slowly and uniformly by a process of continuous recrystallization. Within this temperature range, the uniform dispersion of nano-sized Al 3Sc particles generated by the pre-ageing treatment substantially hinders grain coarsening by Zener pinning of the (sub)grain boundaries. At the higher annealing temperature of 450 °C, certain grains were found to grow discontinuously thereby generating a mixed microstructure consisting of both fine and coarse grains. The data in this study was combined with recent data for a higher solute Al(0.3 wt.% Sc) alloy for furthering our understanding of the time and temperature range in which this family of alloys is resistant to rapid, discontinuous grain coarsening (recrystallization). © 2011 Elsevier Ltd. All rights reserved.